2021
DOI: 10.3390/ijgi10070482
|View full text |Cite
|
Sign up to set email alerts
|

Processing Laser Point Cloud in Fully Mechanized Mining Face Based on DGCNN

Abstract: Point cloud data can accurately and intuitively reflect the spatial relationship between the coal wall and underground fully mechanized mining equipment. However, the indirect method of point cloud feature extraction based on deep neural networks will lose some of the spatial information of the point cloud, while the direct method will lose some of the local information of the point cloud. Therefore, we propose the use of dynamic graph convolution neural network (DGCNN) to extract the geometric features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The contact method is usually installed on a single weighing device on a long conveyor belt frame, and the structure includes a weighing frame, a load cell, a speed sensor, and a totalizer meter. The advantages of this method include low-cost, simple and convenient installation, and no need to make too many changes to the original equipment infrastructure [10][11][12][13]. Scholars have used the discrete element method (DEM) to study the interaction between scraper conveyors and coal flow [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The contact method is usually installed on a single weighing device on a long conveyor belt frame, and the structure includes a weighing frame, a load cell, a speed sensor, and a totalizer meter. The advantages of this method include low-cost, simple and convenient installation, and no need to make too many changes to the original equipment infrastructure [10][11][12][13]. Scholars have used the discrete element method (DEM) to study the interaction between scraper conveyors and coal flow [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extracting information about the vehicle's driving status requires converting the pixel coordinates in the image to world coordinates and calibrating the surveillance camera. Xing et al [25] used dynamic map convolutional neural networks to obtain the position of the target in the point cloud for coordinate transformation under real working conditions. Camera calibration often uses self-calibration techniques based on the extended Kalman filter and the fundamental matrix [26,27].…”
Section: Coordinate Conversionmentioning
confidence: 99%
“…At the same time, the research team of the author has installed a special track to run the inspection robot outside the scraper conveyor and has obtained the point cloud of the coal mine working face by using the light detection and ranging (LiDAR) on the inspection robot. According to the author’s previous research results, the markers in the coal mine working face can be found through DGCNNs, and then, the point cloud coordinate of the coal mine working face can be converted to the geodetic coordinate system . However, further research still needs to be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…According to the author's previous research results, the markers in the coal mine working face can be found through DGCNNs, and then, the point cloud coordinate of the coal mine working face can be converted to the geodetic coordinate system. 48 However, further research still needs to be carried out. Whether DGCNNs can segment the coal wall and the roof and accurately obtain the intersection line of the coal wall and roof has not been known, and whether DGCNNs can achieve a good application effect in the field of energy and geology has also not been known.…”
Section: Introductionmentioning
confidence: 99%